Mix Design For Oil-Palm-Boiler Clinker (OPBC) Concrete (Journal of Science and Technology, 2016)
An experimental investigation was conducted in mix design for lightweight concrete using Oil-Palm-Boiler Clinker (OPBC) as coarse aggregate. ACI mix design as used for normal weight concrete and mix design methods as used for lightweight concrete were employed to obtain the target compressive strength at 28-day and was found to be lower than the target strength for OPBC concrete. It was confirmed that the above established mix design methods couldn’t be used in this new OPBC concrete. Through trial mixes, the acceptable mix designs of this new concrete were obtained. The properties obtained from the acceptable mix designs were slumps of 40 to 100mm, demoulded densities of 1845 to 1980 kg/m3 and the 28-day compressive strengths of 27 to 35MPa.